Livelihood dependency on different Agroforestry Systems in Leh district of Ladakh: Livelihood dependency on different Agroforestry Systems in Leh district in Union territory of Ladakh - udin, meraj (Indian Journal of Agroforestry, 2023)
The present study entitled “livelihood dependency on different agroforestry systems in Leh district of Ladakh ” was carried out, during 2019- 2020. The study site is located between 340 9’ N and 77034’E at an altitude ranging from 2900-5900 meters (amsl). Multistage random sampling technique was used for selection of sampled blocks, villages and households in leh district.A total of 164 households were drawn from sample villages which accounts 25 percent sampling intensity.Among the different agroforestry products apricot fetched the maximum income (1875000 annum-1) followed by barley(1598800 annum-1), buckwheat (1305000 annum-1), vegetables in kharif (1097900 annum-1), apple (1008000 annum-1), fodder (847600 annum-1), walnut (708000 annum-1), fuelwood ( 383350 annum-1), vegetables in rabi(372099.20 annum-1), poles(264366 annum-1), wheat (230000 annum-1), salix poless (189649 annum-1) and NTFP’s(109980 annum-1).The average gross annual income was 142282.57 household-1 annum-1 which comprised of service (21.1%), livestock (20.4%), agriculture (19.7%), fruits (15.3%), business (10.9%), forest resource (7.6%), wage earning (3.8%), others (0.7%) and an average employment opportunities of 778.41mandays annum-1household-1.The correlation co-efficient indicated that among all variables family size, size of land holding, education and livestock possession had significant contribution in influencing the agroforestry resources based livelihood. The study established that the contribution of agroforestry resources in the household economy is inadequate and hence, the promotion of agroforestry is imperative to enhance the livelihood of rural poor on sustainable basis. Hence, the agroforestry deserves a planned and continuous attention of policy makers, scientists, social workers and extensionists for livelihood promotion and development.